Dyskinetic crisis in GNAO1-related disorders: clinical perspectives and management strategies - Domínguez Carral, Jana; Reinhard, Carola; Ebrahimi-Fakhari, Darius; Dorison, Nathalie; Galosi, Serena; Garone, Giacomo; Malenica, Masa; Ravelli, Claudia; Serdaroglu, Esra; van de Pol, Laura A.; Koy, Anne; Leuzzi, Vincenzo; et al. (Frontiers in Neurology, 2024)
Background. GNAO1-related disorders (GNAO1-RD) encompass a diverse spectrum of neurodevelopmental and movement disorders arising from variants in the GNAO1 gene.Dyskinetic crises, marked by sudden and intense exacerbations of abnormal involuntary movements, present a significant challenge in GNAO1-RD.Objectives. This study aimed to establish a standardized framework for understanding dyskinetic crises, addressing crucial aspects such as definition, triggers, diagnostic criteria, complications, and management strategies.